Pattern of Histopathologically Confirmed Uterine and Ovarian Anomeli Among 98 Hysterectomies Attending a Private Medical College Hospital, Dhaka - Sajani, Tabassum Tahmin; Sarnali, Tanjila Tahmin; Rahman, Md Atiqur; Ahmed, Shoib (Anwer Khan Modern Medical College Journal, 2017)
Background: Endometrial diseases ranked among the most common gynecological disorders that affect women globally. This study was undertaken to identify the most common pathologies identified in hysterectomy specimens. Materials & Methods: The present study was conducted in the Department of Pathology, Anwer Khan Modern Medical College, Dhaka over a period of 6 months from July to December 2013. Ninety eight (98) hysterectomy specimens were received by the pathology department during this period. On receiving the hysterectomy specimens, the gross features were noted. A detailed microscopic examination was done to arrive at an accurate diagnosis. Result: Most of the women 54% were 40-49 years age group followed by 25% in 30-39 years age group. Chronic cervicitis and adenomyosis were the commonest pathological findings in (80.6%) and (32.7%) respectively. Other pathologies identified include Leiomyoma (23.5%), endometrial hyperplasia (17.4%), endometrial polyp (4.1%) and PID with hemorrhagic infection (1.0%). Two cases of carcinoma cervix (2.0%), two local invasion of tumors (2.0%) and one adenocarcima (1.0%) was found. Type of operation most common is total hysterectomy with oophorectomy (51.0%). Conclusion: Hysterectomy still remains the widely used treatment modality even in developed countries. The ultimate diagnosis is only on histology, so every hysterectomy specimen should be subjected to histopathological examination. Benign pathologies are more common than their malignant counterparts and the most common pathologies identified in hysterectomy specimens are chronic cervicitis, adenomyosis and leiomyoma. Anwer Khan Modern Medical College Journal Vol. 8, No. 1: Jan 2017, P 6-9